Australia 1:50 000 topographic survey. 5237 3, Watson - Australia. Army. Royal Australian Survey Corps (Canberra : Royal Australian Survey Corps, 1984)
Topographic map on orthophoto base. Relief shown by contours and spot heights.
Marginal mean temperature and rainfall graphs. Index to adjoining sheets.
Keywords: Watson (S.A.) -- Maps; Topographic maps